eMusic - Legal issues concerning downloading music over the Internet - Bechle, Thomas (Department of Commercial Law, 2014)
Sharing music with friends and family has always been a popular activity. Under most copyright laws, sharing physical media with friends and family has always been seen as a 'fair use' - a set of usage patterns that have been traditionally considered to be exceptions to copyright law. With the advent of digital music in the early 1990's sharing of music became redefined. Whereas sharing of physical media meant that only one person could use the media at the same time, sharing digital music involved permanent reproduction of the music files. Thus, sharing digital music equated to reproduction and distribution of music. With the invention of the mp3 standard, the size of digital music files became much smaller without a noticeable compromise of quality. Thus reproduction and distribution of digital music became faster and even easier. [...]